Original paperEnhancement of human skin facial revitalization by moringa leaf extract cream - Ali, Atif; Akhtar, Naveed; Chowdhary, Farzana (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction : Solar ultraviolet exposure is the main cause of skin damage by initiation of reactive oxygen species (ROS) leading to skin collagen imperfection and eventually skin roughness. This can be reduced by proper revitalization of skin enhancing younger and healthier appearance. Aim : To evaluate the skin facial revitalization effect of a cream formulation containing the Moringa oleifera leaf extract on humans. Material and methods: Active cream containing 3% of the concentrated extract of moringa leaves was developed by entrapping in the inner aqueous phase of cream. Base contained no extract. Skin revitalizing parameters, i.e. surface, volume, texture parameters and surface evaluation of the living skin (SELS) were assessed comparatively after application of the base and active cream on human face using Visioscan® VC 98 for a period of 3 months. Results: Surface values were increased by the base and decreased by the active cream. Effects produced for the base and active cream were significant and insignificant, respectively, as observed in the case of surface. Unlike the base, the active cream showed significant effects on skin volume, texture parameters (energy, variance and contrast) and SELS, SEr (skin roughness), SEsc (skin scaliness), SEsm (skin smoothness), and SEw (skin wrinkles) parameters. Conclusions : The results suggested that moringa cream enhances skin revitalization effect and supports anti-aging skin effects.